2008
DOI: 10.1109/tasc.2008.920688
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Dynamic Response Properties of High-Tc Superconducting System: Application for the Maglev Test Vehicle

Abstract: In this paper, we present a simulation process of the melt-texture YBCO high-temperature superconductor (HTS) bulk levitated over the permanent-magnet (PM) guideway, and further experiment also been built to analyze the dynamic behavior of HTS. The relation between suspension force and amplitude of the levitation system under single-degree of freedom vibration environment was investigated, and stiffness was acquired based on the experiment. Besides, equation of motion of the suspension system was presented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Moon et al [14][15][16][17] established a vertical nonlinear dynamic model of maglev system and studied the influence factors of the system vibration. Yang et al [18][19][20] studied the maglev launch system by applying external excitation, and found that the hysteresis effect led to the energy loss in the vibration process. Yang et al [21] studied the vibration characteristics of maglev system under various external excitation by way of a three-dimensional multi-physical field coupling model.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al [14][15][16][17] established a vertical nonlinear dynamic model of maglev system and studied the influence factors of the system vibration. Yang et al [18][19][20] studied the maglev launch system by applying external excitation, and found that the hysteresis effect led to the energy loss in the vibration process. Yang et al [21] studied the vibration characteristics of maglev system under various external excitation by way of a three-dimensional multi-physical field coupling model.…”
Section: Introductionmentioning
confidence: 99%